Problems of Sirri Marriage and Prisoners: A Case Study in Sukadana, East Lampung, Indonesia - Zainuri, Andi; Muslimin, Ahmad; Mukhlishin, Ahmad (El-Usrah: Jurnal Hukum Keluarga, 2023)
Sirri marriage is a marriage carried out using the provisions outlined and determined by custom but does not fulfill state law. The state has established legal marriage through the Marriage Law and the Compilation of Islamic Law (KHI). This study aims to explain the legal perception of sirri marriage from the view of the Compilation of Islamic Law and Marriage Law in Indonesia. This research is an empirical legal study using a statutory approach. The data collection techniques used are interviews and documentation studies. Interviews were conducted with informants with religious leaders, the Head of the Religious Affairs Office, perpetrators of sirri marriage, and community leaders. The study concluded that marriage in Indonesia is legally regulated according to marriage law and the Compilation of Islamic Law, which states that marriage must be recorded. Meanwhile, marriages that are not recorded are not legally valid. The factors that cause the occurrence of sirri marriages are personal factors, including the characteristics of community understanding used as justification, the level of legal awareness factor, namely the level of understanding of community law, and the rules of law that exist and apply in Indonesia, which are less considered. The sirri marriage will have impacts and victims on women and children. Therefore, this research recommends that all parties create legal awareness in the community regarding the legal rules of marriage.